You have the right to be a child: Croatian children's knowledge and attitudes regarding rights of the child - Kuterovac Jagodić, Gordana (2003)
UN Convention on the Rights of the Child is the document that advocates children's rights among which are many that protect and promote child development. The goal of this study was to investigate how children in Croatian postwar and transitional society are informed on their rights, what are their attitudes towards them, and how satisfied they are with the extend of their fulfillment. Differences among children of different age, gender and number of siblings were examined. Participants were 428 elementary and secondary school children aged 9-19 years. Freedom of speech, choice and privacy, free time, play and choice of friends, family, education, home, love and care as well as social care are the rights that were most well known to the participants. Although lots of children believe that children have enough rights (54.4%), 39.2 percent of children believe that children don't have enough rights. Croatian children assessed that their rights are more fulfilled in the families than in school. Children believe that they should be educated about their rights and that the educators should be parents and school, as well as media.
Projekt MZOS
ENG